Analyzing the Plight and Rights of Widows: Exploring the Legal and Social Rights of Hindu Widows (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Every single human being's life is profoundly impacted by the ladies. Safeguarding herimproved natural rights would mean improving an upcoming family, society, and each person. Before theAct of 1956 went into effect, a Hindu female’s estate can be separated into two parts (1) Stridhan, and (2)Hindu Women's estate. The former one was her own property, over which she had complete possession,and it passed to her heirs. The latter was regarded as her restricted or limited estate, over which she hadrestricted alienation rights. Such property passed to the subsequent heirs of the last full owner after herdeath rather than her own heirs. However, Section 14 of the Hindu Succession Act, 1956 detached thelatter cataloguing and granted her absolute ownership over whatever property she had lawfully obtained.In this study, we have talked about the different rights of a Hindu widow and whether a widow can claimrights to her late husband's property. An examination of widow gift eligibility. This paper provides asuccinct outline of the numerous rights of Hindu widows.